Frequency locking in the internal resonance of two electrostatically coupled micro-resonators with frequency ratio 1:3. (1st January 2021) - Wang, Xuefeng; Huan, Ronghua; Zhu, Weiqiu; Pu, Dong; Wei, Xueyong
Highlights: Internal resonance of two electrostatic coupled micro-resonators is investigated experimentally. A phenomenon of frequency locking is observed for the first time at 1:3 frequency ratio. Frequency locking is found to be tunable. Theoretical study is made to explain the frequency locking phenomenon. 7-fold enhancement of the frequency stability is achieved via frequency locking. Abstract: The internal resonance of electrostatically coupled cubic nonlinear low-frequency micro-resonator and linear high-frequency micro-resonator is investigated experimentally. A phenomenon of frequency locking is observed at 1:3 frequency ratio of two resonators for the first time when the coupling strength exceeds a certain value. Then the theoretical study is made to explain the frequency locking phenomenon. Finally, this phenomenon is used to enhance the short-time frequency stability of low-frequency resonator nearly 7-fold.